IMPLEMENTASI WIRAUSAHA BAKSO IKAN BANDENG DITNJAU DARI KESEJAHTERAANYA DI KELURAHAN BAURUNG, KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE PROVINSI SULAWESI BARAT - MUHAMMAD AZIZII (STIE AMKOP, 2020)
Meatballs that are often circulating in the market include beef meatballs, shrimp meatballs, and chicken meatballs. Although fish meatballs have also been circulating in the community, but it is still rare for meatballs to use milk fish as the main ingredient. Park (2004). This research is planned to be carried out at the